1994
DOI: 10.1038/368157a0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane association of Rab5 mediated by GDP-dissociation inhibitor and accompanied by GDP/GTP exchange

Abstract: The Rab GTPases function as specific regulators of membrane transport. The GTP/GDP cycle is believed to control shuttling of Rab proteins between the cytosol and organelle membranes. In vitro, Rab proteins are removed from membranes by a protein that inhibits GDP dissociation (rabGDI), which leads to formation of a cytosolic complex of Rab with the inhibitor protein. Here we use a purified Rab5-rabGDI complex in a permeabilized cell system to investigate how the cytosolic complexed form of Rab reassociates wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
243
0
3

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 294 publications
(257 citation statements)
references
References 16 publications
11
243
0
3
Order By: Relevance
“…Overexpression of GDI can be used to alter the membrane association of rab proteins and thereby affect their function. Excess GDI added in vitro has been demonstrated to release GDP-bound rab proteins from membranes by forming a soluble complex (DiracSvejstrup et al, 1994;Peter et al, 1994;Ullrich et al, 1994). Excess GDI causes a marked inhibition in membrane transport most likely because rebinding of rab proteins to membranes is extremely inefficient under these conditions.…”
Section: Rab11 Is Selectively Released From Membranes By Overexpressementioning
confidence: 99%
“…Overexpression of GDI can be used to alter the membrane association of rab proteins and thereby affect their function. Excess GDI added in vitro has been demonstrated to release GDP-bound rab proteins from membranes by forming a soluble complex (DiracSvejstrup et al, 1994;Peter et al, 1994;Ullrich et al, 1994). Excess GDI causes a marked inhibition in membrane transport most likely because rebinding of rab proteins to membranes is extremely inefficient under these conditions.…”
Section: Rab11 Is Selectively Released From Membranes By Overexpressementioning
confidence: 99%
“…The chloroform phase was collected and the sample re-extracted with the same volume of chloroform. The combined chloroform extract was evaporated and 30 ml 25 mm NH 4 OH added. The presence of geranylgeranyl alcohol was determined by electrospray ionization MS using an LCQ mass spectrometer (Finnigan, San Jose, CA, USA).…”
Section: Expression and Purification Of Tev Proteasementioning
confidence: 99%
“…For their function Rab proteins require modification by geranylgeranyl isoprenoids. This allows them to associate reversibly with a membrane in a tightly controlled fashion [3,4]. Covalent attachment of geranylgeranyl groups to two C-terminal cysteines is catalyzed by Rab geranylgeranyl transferase (RabGGTase).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies suggested the existence of GDF, a factor that would facilitate delivery of Rab-GDP to membranes from the cytosolic GDI-Rab complex (22,26). For example, GDF could be a Rab guanine nucleotide exchange factor(s) (GEF) that promotes Rab activation to the GTPbound form.…”
mentioning
confidence: 99%